Knowledge, attitudes, and positions of religious leaders towards female genital cutting: A cross-sectional study from the Kurdistan Region of Iraq - Mahmood, Kazhan I.; Shabu, Sherzad A.; M-Amen, Karwan; Saleh, Abubakir M.; Ahmed, Hamdia; Mzori, Barzhang Q.; Shabila, Nazar P. (PLOS ONE, 2022)
Background Understanding the perspectives of the key players in the community regarding female genital cutting (FGC) is very important for directing preventive programs. Religious leaders help shape community behaviors, which is highly pertinent in the case of FGC as it is frequently perceived to be a religious requirement. This study assesses religious leaders’ knowledge, attitudes, and positions towards FGC in the Kurdistan Region of Iraq. Methods This cross-sectional study was conducted in the Kurdistan Region of Iraq. It included a purposive sample of 147 local religious leaders (khateebs) representing the three governorates of Erbil, Sulaimaniyah, and Duhok. A self-administered questionnaire was used to collect data about the religious leaders’ knowledge, attitude, and position towards FGC. Results The participants identified reduction of the sexual desire of women as the main benefit (37%) and risk (24%) of FGC. Cultural tradition and religious requirements were the main reported reasons for practicing FGC. About 59% of the religious leaders stated that people ask for their advice on FGC. Around 14% of the participants supported performing FGC, compared to 39.1% who opposed it. Religious (73.9%) and cultural (26.1%) rationales were the main reasons given for supporting FGC. Being a cultural practice with harmful effects (53.5%) and lack of clear religious evidence (46.6%) were the main reasons for being against FGC. Around 52% of the participants recommended banning FGC by law, while 43.5% did not support banning it. A statistically significant association (P = 0.015) was found between religious leaders’ residence and their position on performing FGC. More than 46% of those residing in Duhok were against performing FGC, compared to lower proportions in Erbil (38.8%) and Sulaimaniyah (30%). Conclusion Religious leaders believed that cultural tradition was the main reason behind practicing FGC and they believed that FGC is not common in KRI, and even that it is decreasing. The religious leaders in our study reported that they could have an influential role in the FGC issue due to their position in the community. There was no statistically significant association between religious leaders’ age, education level, or work experience and their position on performing FGC. However, a statistically significant association was found between religious leaders’ residence and their position on performing FGC. A conclusive decision concerning the prohibition of FGC needs to be made by religious authorities. Health awareness activities incorporating FGC risks should be carried out to inform religious leaders at different levels of religious positions. Further research exploring perspectives of religious authorities concerning religious leaders’ inconclusive judgment about FGC is deemed necessary.